Physical Activity-Related Practices and Psychosocial Factors of Childcare Educators: A Latent Profile Analysis - Emma K. Adams; Andrea Nathan; Phoebe George; Stewart G. Trost; Jasper Schipperijn; Hayley Christian (MDPI AG, 2024)
Limited research investigates early childhood education and care (ECEC) educators' involvement in promoting physical activity. The aim was to identify distinct profiles based on physical activity-related practices and psychosocial factors in ECEC educators and examine how they relate to the amount of time allocated to children's physical activity. A secondary analysis of educator-reported survey data from the Play Active study was undertaken. Educators (n = 532) reported on four practices and four psychosocial subscales adapted from the Environment and Policy Evaluation and Observation relating to the provision of physical activity in childcare. Latent profile analysis was used to identify distinct groups of educators based on their practices and psychosocial factors. Logistic regression analysed associations between latent profiles and educator-reported time provided for children's physical activity. Five profiles of educators' physical activity-related practices and psychosocial factors were identified. Profiles with higher practice scores also had higher psychosocial scores. Educators in profiles characterised by higher scores had greater odds of meeting the best practice guidelines for daily time allocated to children for total physical activity and energetic play. This study highlights interventions which address multiple educator behaviour change determinants to improve children's physical activity in childcare.